Q: 3x plus y equals 4 x plus y equals 0?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3x - 2x + 4 = 0 3x - 2x = -4 x = -4

3x + 4y - 4 = 0 y = -2 3x + 4(-2) - 4 = 0 3x - 8 - 4 = 0 3x = 12 x = 4 (4,-2)

(3x-4)(x+5)

(2, -1)

Their graphs are.

Related questions

3x - 2x + 4 = 0 3x - 2x = -4 x = -4

3x + 4y - 4 = 0 y = -2 3x + 4(-2) - 4 = 0 3x - 8 - 4 = 0 3x = 12 x = 4 (4,-2)

The standard form is 3x - 8y - 4 = 0

The standard form is 3x + 8y + 4 = 0

3x-13x+4=0 -10x+4=0 4=10x 4/10=x simplified: x= 2/5

(3x-4)(x+5)

x^2 + 3x + 3 = 7 x^2 + 3x - 4 = 0 (x - 1)(x + 4) = 0 x = 1 or x = -4

(2, -1)

Their graphs are.

x = 4 and y = 0

3x2 + 10x - 8 = 0 3x2 + 12x - 2x - 8 = 0 3x(x + 4) - 2(x + 4) = 0 (3x - 2)(x + 4) = 0 So 3x - 2 = 0 or x + 4 = 0 so x = 2/3 or x = -4

3x+56 = 2x+4 3x-2x = 4-56 x = -52